Analisis Perbandingan Brand Equity Jual Beli Online pada Aplikasi Tokopedia dan Shopee di Kota Bandung - Favian Muhammad Gaus; Adhi Prasetio (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2021)
This study aims to find out the equity comparison of Shopee and Tokopedia e-commerce brands, brand equity itself has four dimensions including Brand Asosciation, Perceived Quality, Brand Loyalty and Brand Awareness. This study uses a quantitative method, data collection in this study using questionnaire Sampling Purposive Method by taking samples intercepted by 100 respondents. Data Analysis Techniques using descriptive analysis and Whitney Man Test data using IBM 26 SPSS Statistics. Based on the results of the research that has been carried out, it can be concluded that there are differences in the brand equity of Tokopedia and Shopee based on the dimensions where the store is superior to the Brand Loyalty dimension, while the Shopee itself is higher in terms of the dimensions of Brand Awareness, Brand Association and Perceived Quality from the Tokopedia. Tokopedia can increase these three dimensions by doing promotions using their social media, providing education about their applicationand also using influencers to facilitate promotion about the Tokopedia application while for shopees themselves, they can give gifts to memberships who have long transacted in their application. Keywords: Brand Equity, Brand Awareness, Brand Association, Brand Loyalty, Perceived Quality.